Concentration of amoxicillin in maternal serum, cord blood, amniotic fluid and the placenta after vaginal administration. (22nd November 2015) - Zaręba-Szczudlik, Julia; Romejko-Wolniewicz, Ewa; Lewandowski, Zbigniew; Różańska, Hanna; Czajkowski, Krzysztof
Abstract: Objective : The aim of this study was to assess the amoxicillin concentration in maternal serum, cord blood, amniotic fluid and the placenta, 2 h following vaginal administration and the factors influencing the drug level. Methods : Twenty-eight full-term pregnant women who qualified for elective cesarean delivery were included in the study. Vaginal suppositories containing 250 mg of amoxicillin were administered 2 h prior to the operation. Amoxicillin levels were determined using the diffusion microbial assay. Results : The amoxicillin level in amniotic fluid was significantly higher in comparison to that of maternal serum, cord blood or the placenta. Maternal age positively and gestational weight gain negatively correlated with the amoxicillin concentration in maternal serum. The maternal serum hemoglobin level and red blood cell count were positively correlated with amoxicillin concentration in the amniotic fluid. Neonatal birth weight was positively correlated with maternal serum and cord blood amoxicillin levels. Hypertensive women had significantly higher amoxicillin concentrations in amniotic fluid, and women with thrombocytopenia presented significantly higher cord blood amoxicillin concentrations. Conclusions : Amoxicillin presented poor concentration in maternal–fetal compartments after vaginal administration, but the factors influencing the drug level in different compartments require further investigation.